2004
DOI: 10.1002/mame.200400145
|View full text |Cite
|
Sign up to set email alerts
|

Morphology Dependent Double Yielding in Injection Molded Polycarbonate/Polyethylene Blend

Abstract: Summary: Polycarbonate (PC)/polyethylene (PE) blend was injection molded at different molding temperatures. The morphological observation by scanning electronic microscope (SEM) indicated that the sample molded at 190 °C contained only uniformly dispersed spherical PC particles. The samples molded at 230 and 275 °C had a typical skin‐core structure, and there were many injection‐induced PC fibers in the subskin. While the sample molded at 190 °C had the usual stress‐strain behavior, the samples obtained at 230… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
29
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 36 publications
1
29
0
Order By: Relevance
“…The neat PE and PE5 are very ductile and the ultimate ruptures have not been achieved due to the limit of the distance between two crossheads. They shows similar stress‐strain behaviors except a slight higher yield stress for PE5, indicating some reinforcement of PC on PE 30. In addition, PE5 displays a typical single yield behavior as neat PE does.…”
Section: Resultsmentioning
confidence: 83%
See 3 more Smart Citations
“…The neat PE and PE5 are very ductile and the ultimate ruptures have not been achieved due to the limit of the distance between two crossheads. They shows similar stress‐strain behaviors except a slight higher yield stress for PE5, indicating some reinforcement of PC on PE 30. In addition, PE5 displays a typical single yield behavior as neat PE does.…”
Section: Resultsmentioning
confidence: 83%
“…Typical anisotropic skin‐core structures were observed for all the blends as in many other injection‐molded blends,33–42 in which the dispersed PC particles exhibit different shapes and sizes in the core, sub‐skin, and intermediate layers. Although the phase viscosity ratio (ratio of viscosity of the dispersed phase to that of the matrix) is more than one,43 amorphous PC particles can deform under strong shear and elongational fields 30. In the core layer, most PC particles remained spherical in shape except a few slightly deformed ones, as shown in Figure 2.…”
Section: Resultsmentioning
confidence: 96%
See 2 more Smart Citations
“…The mechanism of double yielding is related to the microstructure of the polymer and there exist three plausible mechanisms to explain this behavior 39. Li et al detected a double yielding behavior in structurally different injection molded polycarbonate/high‐density polyethylene blends based on their morphology, where the first yield point was due to the high‐density polyethylene and the second yield point was attributed to the injection molded polycarbonate fibers 40–42. It is suggested that a similar reason may be proposed for the all‐PP composites, where the copolymer matrix may be responsible for the first yielding and the reinforcing PP homopolymer responsible for the second yield point.…”
Section: Resultsmentioning
confidence: 99%